Relationship between interfacial stress and thermal expansion coefficient of copper–matrix composites with different reinforced phases. (February 2014) - Song, K.; Guo, X.; Liang, S.; Zhao, P.; Zhang, Y.
<x content-type="archive" xml:space="preserve">Abstract</x> Copper–matrix composites reinforced with Al2O3, SiO2, SiC and MgO nanoparticles were fabricated using powder metallurgy. The effects of the different nanoparticles on the thermal expansion behaviour of the composites were examined. The thermal expansion properties of the composites were evaluated using the coefficient of thermal expansion from 50 to 500°C. The relationship between interface stress and coefficient of thermal expansion of the copper–matrix composites with various reinforced phases was determined using theoretical models and experimental data. The results show that introducing dispersed nanoparticles into the copper matrix can significantly reduce the coefficient of thermal expansion. By contrast, increasing the temperature increases the thermal expansion coefficient of the copper–matrix composites and the interfacial pressure between the reinforcements and the copper matrix. The calculated pressure values at the nanoparticle–copper matrix interface suggest that plastic deformation occurred in the temperature range from 200 to 250°C for the SiO2/Cu and SiC/Cu composites and at 350°C for the MgO/Cu and Al2O3/Cu composites. These values are consistent with the variations observed in the measured coefficient of thermal expansion.